Gastric vagal motoneuron function is maintained following experimental spinal cord injury - Swartz, Emily M. (Neurogastroenterol Motil, 2014)
BACKGROUND: Clinical reports indicate that spinal cord injury (SCI) initiates profound gastric dysfunction. Gastric reflexes involve stimulation of sensory vagal fibers, which engage brainstem circuits that modulate efferent output back to the stomach, thereby completing the vago-vagal reflex. Our recent studies in a rodent model of experimental high thoracic (T3-) SCI suggest that reduced vagal afferent sensitivity to gastrointestinal (GI) stimuli may be responsible for diminished gastric function. Nevertheless, derangements in efferent signals from the dorsal motor nucleus of the vagus (DMV) to the stomach may also account for reduced motility. METHODS: We assessed the anatomical, neurophysiological and functional integrity of gastric-projecting DMV neurons in T3-SCI rats using: 1) retrograde labeling of gastric-projecting DMV neurons; 2) whole cell recordings from gastric-projecting neurons of the DMV; and, 3) in vivo measurements of gastric contractions following unilateral microinjection of thyrotropin releasing hormone (TRH) into the DMV. KEY RESULTS: Immunohistochemical analysis of gastric-projecting DMV neurons demonstrated no difference between control and T3-SCI rats. Whole cell in vitro recordings showed no alteration in DMV membrane properties and the neuronal morphology of these same, neurobiotin-labeled, DMV neurons were unchanged after T3-SCI with regard to cell size and dendritic arborization. Central microinjection of TRH induced a significant facilitation of gastric contractions in both control and T3-SCI rats and there were no significant dose-dependent differences between groups. CONCLUSIONS: Our data suggest that the acute, 3 day to 1 week post-SCI, dysfunction of vagally-mediated gastric reflexes do not include derangements in the efferent DMV motoneurons.